TEACHERS’ PERCEPTION ON TECHNOLOGY INTEGRATION AND ITS AVAILABILITY IN PRESCHOOL LEARNING ENVIRONMENT - Ailyn T. Gilay; Aizabeth S. Anga (European Journal of Education Studies, 2025)
This study assessed teachers' perceptions of the integration of technology into the learning process and its availability in the preschool learning environment at a public elementary school in the province of Cebu, Philippines, for the school year 2025–2026, using a descriptive correlational research design. 54 teachers completed the adopted questionnaire, which served as the primary data collection tool. The study employed descriptive and inferential statistics, including the weighted mean, standard deviation, and Pearson’s r, for data analysis. Results revealed that the respondents had very positive perceptions of technology integration in terms of their beliefs, and also positive perceptions of their knowledge and attitudes towards technology integration. On the other hand, the respondents claimed that technology resources are sometimes available in the learning process. Moreover, there was a weakly significant correlation between the respondents’ perception of technology integration and the availability of technology resources in the preschool learning environment. Hence, school administrators need to ensure sufficient technology resources for teachers’ utilization in the teaching-learning process. Article visualizations: